Workbooks in chemistry : - Walton, Paul H. (Oxford Univ. Press, 1998)
This book is the workbook designed to develop student's ability and confidence in using group theory in chemistry. It introduces the key concepts of this pivotal area of chemistry, and has separate sections on molecular symmeter, the mathematics of group theory, and the use of group theory in chemistry.